PENGARUH KUALITAS PRODUK IM3 TERHADAP TINGKAT KEPUASAN PELANGGAN PADA PT. TECHNOMAS INTERNUSA CABANG XXX - KASINO MARTOWINANGUN KASINO MARTOWINANGUN; DERENA PURWANINGSIH DERENA PURWANINGSIH (EKBIS (Ekonomi & Bisnis), 2019)
This research aimed to determine the effect of quality Im3 products to the level of customer satisfaction at PT. Technomas Internusa Branch XXX. The methods used in this research was observation and questionnaires, and then tested the truth with the scientifically theory then concluded. The results of analysis this research indicate that of coefficient determination show the influenced very strong between product quality and the level of customer satisfaction that is 87,6% and the remaining 12,4% is influenced by other factors not examined in this research. The suggestions submitted to the company are to constantly improve product quality especially on signal strength and to expand network coverage improving customer satisfaction, as well as improving product performance to avoid interruption when used, and maintain customer satisfaction when communicating using Im3 products.